A study of manpower issues in project management - Lim, Hui Mui; Tan, Poh Yeng; Tan, Pui San; Mohd Nawi, Mohd Nasrun (2013)
This article is about factors of manpower issue in project management that affect the project running.Lacking of manpower will delay or suspend the progress of a project.The cause of lacking manpower can be ranged from base workers until the top management board of a company.Thus we need to minimize project delays and make recommendations for effective projects.We distributed 25 sets of survey questionnaires for data collection and do data analysis by calculating Relative Importance Index (RI).The result shown that contractor factor occupied the largest capacity among all factors.